Gambaran Gejala Klinis Pasien Terkonfirmasi Covid-19 Di Rsud H. Abdul Moeloek Bandar Lampung - Ribka Wulandari; Deviani Utami; Akhmad Kheru (Malahayati Nursing Journal, 2022)
ABSTRACT Covid-19 is an infectious disease caused by the newly discovered corona virus. There are several symptoms that are often caused by Covid-19, including: fever, dry cough, shortness of breath, muscle aches, stuffy nose, flu, headache, conjunctivitis, sore throat, diarrhea and skin rashes. The heaviest cases in COVID-19 patients can cause acute respiratory distress syndrome (ARDS), sepsis and septic shock, multi-organ failure, including acute kidney or heart failure and even death. To find out the description of the clinical symptoms of patients with confirmed COVID-19 at H. Abdul Moeloek Hospital Bandar Lampung in 2021. The  type of research used in this research is descriptive quantitative with this research design using cross-sectional. Sampling was done by purposive sampling method and 300 people met the inclusion criteria. Data analysis using univariate test. It is known that most of the respondents were male (52.3%), aged 46-55 years (20.7%), the most common symptom was cough (75.33%), did not have comorbidities (68%). ), the most chest X-ray images in Covid-19 patients were infiltrates (80.3%), had normal. From the results of the univariate analysis, it was found that the clinical symptom description in patients with confirmed Covid-19 at the H. Abdul Moeloek Hospital Bandar Lampung illustrates that the moderate symptom group is the highest severity with the most common symptoms being cough, fever, shortness of breath and anosmia. Of the 300 samples of confirmed COVID-19 patients, 37 patients died from comorbidities, namely hypertension experienced in the late elderly (56-65 years) and seniors ( 65 years). It is recommended that the public is expected to increase their knowledge about the clinical symptoms of confirmed COVID-19 patients, handling confirmed COVID-19 patients, using masks, maintaining distance, how to wash hands, and vaccinating.  Keywords: Knowledge, education, COVID-19, vaccination COVID-19. ABSTRAK Coronavirus Disease 2019 (COVID-19) adalah penyakit menular yang disebabkan Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Penanganan COVID-19 yang harus dilaksanakan salah satunya vaksin COVID-19. Tujuan vaksinasi adalah mengurangi penularan, menurunkan angka kesakitan, kematian, mencapai kekebalan kelompok di masyarakat dan melindungi masyarakat dari COVID-19. Namun berdasarkan hasil presurvei didapatkan 7 (70%) dari 10 (100%) orang tidak patuh dilakukan vaksinasi COVID-19. Diketahui hubungan tingkat pengetahuan dan pendidikan terhadap kepatuhan divaksinasi COVID-19 pada masyarakat wilayah kerja Puskesmas Rajabasa Indah Tahun 2021. Penelitian kuantitatif menggunakan penelitian analitik observasional dengan pendekatan cross sectional. Pengambilan sampel menggunakan teknik accidental sampling sebanyak 214 responden dengan kuesioner selanjutnya dianalisis menggunakan uji Chi- Square. Didapatkan distribusi pengetahuan dan pendidikan dari 214 responden paling banyak pengetahuan baik 117 (54,7%) responden, pendidikan tinggi 112 (52,3%) responden, dan distribusi kepatuhan didapatkan terbanyak patuh divaksinasi COVID-19 132 (61,7%) responden. Dari hasil analisis univariat diperoleh bahwa gambaran gejala klinis pada pasien yang terkonfirmasi Covid-19 di RSUD H. Abdul Moeloek Bandar Lampung menggambarkan bahwa kelompok gejala sedang menjadi tingkat keparahan tertinggi dengan gejala tersering batuk,demam,sesak serta anosmia. Dari 300 sampel pasien terkonfirmasi covid-19 sebanyak 37 pasien meninggal akibat penyakit penyerta yaitu hipertensi yang dialami pada usia lansia akhir (56-65 tahun) dan manula ( 65 tahun ). Disarankan bagi masyarakat diharapkan menambah pengetahuan mengenai  gambaran gejala klinis pasien yang terkonfirmasi COVID-19, penanganan pasien terkonfirmasi COVID-19, penggunaan masker, menjaga jarak, cara mencuci tangan, serta melakukan vaksinasi.Kata Kunci: Pengetahuan, pendidikan, COVID-19, vaksinasi COVID-19